WOMEN'S FEELING OF SECURITY AND RIGHT TO SELF-DETERMINATION: HOW DO TODAY'S BEAUTY VLOGGERS EMPOWER WOMEN IN DIGITAL AGE? - Suryani, Adi; Soedarso, Soedarso; Rizkiantono, Raditya Eka; Nisa, Khairun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Recently, many women are suffering from women-body related issues, such as body shaming, bullying social discrimination or unequal treatment at workplaces. This frequently provokes women to devote high energy and effort to meet the beauty standards which are imaged by many media advertisement, social comparison and norm. This study aims to explore how several beauty vloggers empower other women by educating them to feel secure with their own selves and develop sense of self-determination. This study adopts a qualitative research method. The study finds that the beauty vloggers are empowering the women to feel secure, develop self-love and self-acceptance and be aware of beauty diversity. They are also giving some insights into the importance of health and holistic wellness in beauty. Beauty is also understood within the context of women rights through beauty democratization in which all women can develop their own beauty relativism or subjectivism.